The role of SDF‐1 in homing of human adipose‐derived stem cells. Issue 1 (13th February 2015) - Stuermer, Ewa K.; Lipenksy, Alexandra; Thamm, Oliver; Neugebauer, Edmund; Schaefer, Nadine; Fuchs, Paul; Bouillon, Bertil; Koenen, Paola
Abstract One of the putative pathophysiological mechanisms of chronic wounds is a disturbed homing of stem cells. In this project, the stromal cell‐derived factor 1 (SDF‐1)/C‐X‐C chemokine receptor (CXCR) 4 and SDF‐1/CXCR7 pathway were focused in human adipose‐derived stem cells (ASCs). ASCs were incubated with acute (AWF) or chronic wound fluid (CWF) to analyze their effects by quantitative real‐time polymerase chain reaction (SDF‐1, CXCR4, CXCR7, TIMP3), enzyme‐linked immunosorbent assay (SDF‐1 in WFs and supernatant), and transwell migration assay with/without antagonization. Whereas SDF‐1 amounted 73.5 pg/mL in AWF, it could not be detected in CWF. Incubation with AWF led to a significant enhancement (129.7 pg/mL vs. 95.5 pg/mL), whereas CWF resulted in a significant reduction (30 pg/mL vs. 95.5 pg/mL) of SDF‐1 in ASC supernatant. The SDF‐1 receptor CXCR7 was detected on ASCs. AWF but not CWF significantly induced ASC migration, which was inhibited by CXCR4 and CXCR7 antagonists. Expressions of SDF‐1, CXCR4, and CXCR7 were significantly stimulated by AWF while TIMP3 expression was reduced. In conclusion, an uncontrolled inflammation in the chronic wound environment, indicated by a reduced SDF‐1 expression, resulted in a decreased ASC migration. A disturbed SDF‐1/CXCR4 as well as SDF‐1/CXCR7 pathway seems to play an important role in the impaired healing of chronic wounds.